PENGARUH PERTAMBANGAN PASIR TERHADAP EROSI DAN SEDIMENTASI SUNGAI (STUDI KASUS DI DESA TANJUNG ALAM KECAMATAN SEI DADAP KABUPATEN ASAHAN) - Muslich Muchlish; I.A. Faisyal; Sri Sunarsih (Eksergi, 2021)
Sand mining in Tanjung Alam Village, Sei Dadap District, Asahan Regency, which is carried out with a suction machine is thought to have a negative impact on the environment. This study aims to examine the effect of sand mining on erosion and sedimentation in that river. The analysis steps begins with measuring the river profile, measuring flow velocity, measuring river discharge, measuring sediment concentration, measuring rainfall, measuring slope and calculating the estimated rate of erosion. To calculate the estimated erosion rate in this study using the USLE method and to calculate the sediment load using SNI 3414: 2008 with the depth-integrating technique. Based on the calculation results, it is known that sand mining activity causes narrowing of the river profile, accelerates river flow, increases river discharge so that it increases the rate of erosion, and sedimentation. The highest sediment load value is at point 5 which is located downstream of mining 1 and 2 with a value of 2922.48 tons/day. While the highest estimated erosion rate is at point 5 with a value of 125.9 tons/ha/year which is included in the heavy category. Measurements at each sampling point prove that sand mining activities have a high impact on increasing the rate of erosion and sedimentation in rivers.